Mapping problem and requirements to final solution: A document analysis of capstone design projects. Issue 4 (October 2019) - Joshi, Shraddha; Morkos, Beshoy; Summers, Joshua D
Formulating and solving engineering problems and designing solutions that meet the established requirements are important skills that graduating engineering students need to possess. However, there are noticeable gaps in the literature with respect to understanding how the formulation of design problems and establishment of requirements affect the final design solution in undergraduate design education. This paper is an initial step to understand the influence of the content volume of the problem statement and requirements on the content volume of the final solution in capstone design projects. Content volume was used as a measure for this study as it provided a more objective way to measure the relation between problem statement, requirements, and final solutions as compared to other measures such as quality that are more subjective. In doing so, a document analysis of final reports from capstone design class collected over a period of 10 years is conducted. The findings of this research indicate that a low content volume of problem statement and requirements leads to no greater than a medium content volume in the final solution, whereas, a high content volume of final solution is more likely to result from either a high or medium content volume of problem statement and requirements. These findings are used to make several recommendations. Incorporating these recommendations while teaching capstone design classes can help students to improve the content volume of the problem statement and requirements. Thus, this assists in improving students' skills of formulating detailed problem statements and establishing requirements for their projects.